Islamic tolerance and the West: early encounters and influences - Naseri, Fahimeh (Universiti Kebangsaan Malaysia, 2014)
This article is an attempt to explore the conception of tolerance as an inherent principle of Islam, and to show how it was practised when Islam was a political and cultural power. It will be argued that Muslim practice of religious and cultural tolerance proves to be one of the very first examples of multiculturalism and inclusion. The early instances of delivering this Islamic value in Spain, Turkey and during the Second Crusade provide evidence for the Muslim contribution to religious and cultural inclusion which is part of the belief system of Muslims.